Novel approach towards the synthesis of carbon-based transparent highly effective flame retardant. (November 2018) - Khose, Rahul V.; Pethsangave, Dattatray A.; Wadekar, Pravin H.; Ray, Alok K.; Some, Surajit
Abstract: In this article, a novel and facile method is proposed to synthesize a highly effective carbon-based water dispersible flame retardant. This is the first report of carbon-based highly potent transparent flame retardant, which keeps the colour of the cloth intact. A functionalized flame retardant graphene quantum dots (FR-GQD) as a carbon-based material was synthesized using graphene oxide and phosphorous source through a hydrothermal treatment. As prepared transparent FR-GQD solution coated cotton cloth was found to maintain cloth's original colour. In a flame test, FR-GQD coated cloth emitted little smoke initially and after that, it failed to catch fire for more than 300 s and maintained its initial shape. Whereas the control cloth caught fire and burnt completely within 15 s. Flame retardant efficiency of the FR-GQD coated cloth was confirmed by detail flame tests such as limiting oxygen index (LOI), exposure to high heat flux (∼50 kW/cm 2 ) and turbulent premixed flame at high temperature (∼1400  ° C). The strength of FR-GQD coated cloth was determined using tensile strength test. This technique of synthesis and application of this water dispersed FR material may find a general approach towards the practical and eco-friendly application of non-toxic FR-GQD as transparent flame retardant. Graphical abstract: Image 1